THE FUNCTION OF TAREKAT IN EDUCATING THE SOUL - Muhammad Rifa Badawi (Alhamdulillah : Jurnal Agama Islam, 2026)
This study examines the function of tarekat in educating the soul by positioning tarekat as a method of spiritual formation within Islamic education. The purpose of the study is to explain the function of soul education carried out by tarekat through the perspectives of Islamic education, exact metaphysics, and Islamic Sufism. The study employs a descriptive qualitative approach with a library research design. The data were analyzed through source selection, thematic classification, analytical reading, and the construction of conceptual synthesis. The findings show that tarekat functions to organize dhikr, mujahadah, muhasabah, muraqabah, adab, guidance by a mursyid, and social responsibility into a holistic process of soul education. From the perspective of Islamic education, tarekat operates as the habituation of values and the formation of moral character. From the perspective of exact metaphysics, tarekat is understood as an ordered and gradual path that connects the outward and inward dimensions of the human being. From the perspective of Islamic Sufism, tarekat becomes a means of tazkiyat al-nafs toward a soul that is tranquil, aware, and well-mannered. This study affirms that tarekat remains relevant to contemporary Islamic education as long as it is grounded in sharia, adab, chains of scholarly transmission, and moral formation.